Amplification Self-Adjustment: Controls and Repeatability. Issue 3 (13th May 2022) - Boothroyd, Arthur; Retana, Jennifer; Mackersie, Carol L.
Abstract : Objectives: This study was a continuation of work on an explore-and-select approach to the self-adjustment of amplification. Goals were to determine (i) the effect of changing the number of adjustment controls from three to two, (ii) the effect of changing the initial adjustment from overall output to high-frequency output, (iii) individual repeatability, (iv) the effect on phoneme recognition of increasing and decreasing overall output relative to the starting and adjusted conditions, and (v) listener reactions to, and opinions of, the self-adjustment procedure. Design: Twenty-two adults with hearing loss, 10 of whom were hearing aid users, adjusted level and spectrum of connected speech to preference, using three configurations of number and order of adjustment parameters. The three adjustments were replicated to give a total of six. Presentation was monaural, in quiet, using the ear with the better threshold at 2 kHz. The starting condition was a generic prescription for a typical mild-to-moderate hearing loss. Real ear output spectra were measured for the 6 self-adjustments, the generic starting condition, and the individual NAL-NL2 prescriptions for speech at 65 dB SPL. Monaural phoneme recognition in monosyllables was assessed, in quiet, at levels of −14, −7, 0 and +7 dB relative to both the starting and the self-adjusted conditions. Participants completed a questionnaire and their comments on each question were transcribed. Results: Changing the number of listener controls from 3 to 2 reduced mean adjustment time by around 50% but had negligible effect on group-mean output response. Starting adjustment with high-frequency output rather than overall output resulted in a 2 to 3 dB reduction of group-mean self-adjusted output below 1 kHz. Individual self-adjustments were within ±5 dB of NAL-NL2 prescription (for a 65 dB SPL speech input) for two-thirds of the participants in the high frequencies and for just over half in the low frequencies. In six self-adjustments, individuals self-adjusted, on average, to within ±4 dB of their own mean in both high and low frequencies. There was no evidence that these findings differed for hearing aid users and nonusers. Changes of overall output by ±7 dB after self-adjustment did not significantly affect group mean phoneme recognition. Preference for number and order of self-adjustment differed among participants, as did opinions on self-fitting of hearing aids. Conclusions: These findings support the conclusion that, for many adults with hearing loss, an explore-and-select procedure for self-adjustment of amplification leads to output values that are repeatable within a few dB, are relatively immune to the number and order of adjustment parameters, and place the average listener well along the plateau of a phoneme recognition versus amplitude function.